Inactivation of the superior cerebellar peduncle blocks expression but not acquisition of the rabbit's classically conditioned eye-blink response. - Krupa, D J (1995)
The localization of sites of memory formation within the mammalian brain has proven to be a formidable task even for simple forms of learning and memory. Recent studies have demonstrated that reversibly inactivating a localized region of cerebellum, including the dorsal anterior interpositus nucleus, completely prevents acquisition of the conditioned eye-blink response with no effect upon subsequent learning without inactivation. This result indicates that the memory trace for this type of learning is located either (i) within this inactivated region of cerebellum or (ii) within some structure(s) efferent from the cerebellum to which output from the interpositus nucleus ultimately projects. To distinguish between these possibilities, two groups of rabbits were conditioned (by using two conditioning stimuli) while the output fibers of the interpositus (the superior cerebellar peduncle) were reversibly blocked with microinjections of the sodium channel blocker tetrodotoxin. Rabbits performed no conditioned responses during this inactivation training. However, training after inactivation revealed that the rabbits (trained with either conditioned stimulus) had fully learned the response during the previous inactivation training. Cerebellar output, therefore, does not appear to be essential for acquisition of the learned response. This result, coupled with the fact that inactivation of the appropriate region of cerebellum completely prevents learning, provides compelling evidence supporting the hypothesis that the essential memory trace for the classically conditioned eye-blink response is localized within the cerebellum.